Assessment of Debris Extrusion in Curved Canals: An In Vitro Analysis of Various Single-File Endodontic Instrumentation Systems - Muhammad Zubair Ahmad (International Journal of Dentistry)
Objectives. Rotary single-file endodontic systems are commonly used for root canal treatment. However, very few studies have evaluated the apical extrusion of debris generated by these systems during canal preparation at normal body temperature in laboratory conditions. The aim of this study was to evaluate the amount of apically extruded debris caused by seven different single-file endodontic instrumentation systems at body temperature in mandibular molar teeth with curved root canals. Methods. One hundred forty mandibular first permanent molars were randomly divided into seven groups (n = 20) to be prepared by one of the following systems at 35°C: Reciproc Blue (REC Blue), WaveOne Gold (WOG), One Reci (OR), Neoniti, HyFlex EDM (HEDM), One Curve (OC), or XP Shaper (XPS). Debris was collected into preweighted Eppendorf tubes. The weight of the extruded debris was recorded by subtracting the weight of the tooth-free apparatus from the post-procedure weight. Data were analyzed by one-way ANOVA and Tukey’s tests (p <5%). Results. REC Blue, WOG, and OR groups extruded significantly more debris from the apex than XPS, OC, and Neoniti groups (p <0.05). No significant difference was observed among the XPS, OC, Neoniti, and HEDM groups (p >0.05). Conclusion. All the instruments were associated with debris extrusion. However, REC Blue, WOG, and OR extrude significantly more debris than other instruments. The amount of debris with different files was REC Blue > OR > WOG > HEDM > OC > Neoniti > XPS. XPS, Neoniti, and OC caused significantly less extrusion of debris than REC Blue, WOG, and OR.